Inflamm-aging and arachadonic acid metabolite differences with stage of tendon disease - Dakin, S; Dudhia, J; Werling, N; Werling, D; Abayasekara, DR; Smith, R (Public Library of Science, 2012)
The contribution of inflammation to the pathogenesis of tendinopathy and high prevalence of re-injury is not well established, although recent evidence suggests involvement of prostaglandins. We investigated the roles of prostaglandins and inflammation-resolving mediators in naturally occurring equine tendon injury with disease stage and age. Levels of prostaglandins E2 (PGE2), F2α (PGF2α), lipoxin A4 (LXA4) and its receptor FPR2/ALX were analysed in extracts of normal, sub-acute and chronic injured tendons. To assess whether potential changes were associated with altered PGE2 metabolism, microsomal prostaglandin E synthase-1 (mPGES-1), prostaglandin dehydrogenase (PGDH), COX-2 and EP4 receptor expression were investigated. The ability of tendons to resolve inflammation was determined by assessing FPR2/ALX expression in natural injury and IL-1β stimulated tendon explants. Alterations in the profile of lipid mediators during sub-acute injury included low PGE2 and elevated LXA4 levels compared to normal and chronic injuries. In contrast, PGF2α levels remained unchanged and were three-fold lower than PGE2. The synthetic capacity of PGE2 as measured by the ratio of mPGES-1:PGDH was elevated in sub-acute injury, suggesting aberrations in tendon prostaglandin metabolism, whilst COX-2 and EP4 receptor were unchanged. Paradoxically low tendon PGE2 levels in early injury may be attributed to increased local clearance via PGDH or the class switching of lipid mediators from the prostaglandin to the lipoxin axis. PGE2 is therefore implicated in the development of tendon inflammation and its ensuing resolution. Whilst there was no relationship between age and tendon LXA4 levels, there was an age-associated decline in FPR2/ALX receptor expression with concurrent increased PGE2 levels in injury. Furthermore, uninjured tendon explants from younger (<10 years) but not older horses (≥10 years) treated with IL-1β responded by increasing FPR2/ALX suggesting aged individuals exhibit a reduced capacity to resolve inflammation via FPR2/ALX, which may present a potential mechanism for development of chronic tendinopathy and re-injury.